LEXICAL TRANSLATION TRANSFORMATIONS IN WRITTEN TRANSLATION: APPLICATION AND ANALYSIS IN LEGAL TEXTS - Kalonov Mirzoxid Isamiddin o’g’li; Saidova Gulyora Abduhakimovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
Written legal translation demands both linguistic expertise and a comprehensive understanding of legal systems, cultural contexts, and specialized terminologies to ensure precise conceptual transfer. Lexical transformations, which involve systematic modifications at the word or phrase level, play a crucial role in adapting legal content to the linguistic and normative standards of the target language while preserving legal equivalence and interpretative consistency. This article examines the application of such transformations in written legal translation, drawing on examples from treaties and resolutions. It further explores strategies such as transliteration, calque, borrowing, and substitution, emphasizing their significance in enhancing clarity, accuracy, and functional adequacy to facilitate cross-cultural legal communication.